Savings for visuomotor adaptation require prior history of error, not prior repetition of successful actions - Leow, L.; de Rugy, A.; Marinovic, Welber; Riek, S.; Carroll, T. (American Physiological Society, 2016)
When we move, perturbations to our body or the environment can elicit discrepancies between predicted and actual outcomes. We readily adapt movements to compensate for such discrepancies, and the retention of this learning is evident as savings, or faster readaptation to a previously encountered perturbation. The mechanistic processes contributing to savings, or even the necessary conditions for savings, are not fully understood. One theory suggests that savings requires increased sensitivity to previously experienced errors: when perturbations evoke a sequence of correlated errors, we increase our sensitivity to the errors experienced, which subsequently improves error correction (Herzfeld et al. 2014). An alternative theory suggests that a memory of actions is necessary for savings: when an action becomes associated with successful target acquisition through repetition, that action is more rapidly retrieved at subsequent learning (Huang et al. 2011). In the present study, to better understand the necessary conditions for savings, we tested how savings is affected by prior experience of similar errors and prior repetition of the action required to eliminate errors using a factorial design. Prior experience of errors induced by a visuomotor rotation in the savings block was either prevented at initial learning by gradually removing an oppositely signed perturbation or enforced by abruptly removing the perturbation. Prior repetition of the action required to eliminate errors in the savings block was either deprived or enforced by manipulating target location in preceding trials. The data suggest that prior experience of errors is both necessary and sufficient for savings, whereas prior repetition of a successful action is neither necessary nor sufficient for savings.